2017
DOI: 10.1111/ibi.12547
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behaviour of Magellanic Penguins during the early chick‐rearing period at Isla de los Estados, Argentina

Abstract: Studies of the at‐sea distribution and trophic ecology of penguins are essential to understand their role in the broader marine food web. Magellanic Penguins Spheniscus magellanicus have a wide distribution and their foraging behaviour varies across breeding sites and between sexes, among others. In this study, we characterized the at‐sea areas, the diving strategies and the relative trophic level of Magellanic Penguins breeding at Isla de los Estados, Argentina, during the early chick‐rearing period. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 81 publications
0
4
1
Order By: Relevance
“…We also show invasive herbivores contribution in breeding and nonbreeding season in white (median and 95% credible interval, (e) within the overall terrestrial estimate variation in prey signatures and no variation in tissue-specific turnover rates since contemporary sampling of both consumers and preys was not possible due to logistical reasons. In our study site, temporal variation in isotopic ratio in seabirds was observed (Harris et al, 2016;Rosciano et al, 2018Rosciano et al, , 2019. However, interannual differences observed (especially in δ 13 C) were lower than the differences we observed for marine and terrestrial prey items.…”
Section: Limitationscontrasting
confidence: 64%
“…We also show invasive herbivores contribution in breeding and nonbreeding season in white (median and 95% credible interval, (e) within the overall terrestrial estimate variation in prey signatures and no variation in tissue-specific turnover rates since contemporary sampling of both consumers and preys was not possible due to logistical reasons. In our study site, temporal variation in isotopic ratio in seabirds was observed (Harris et al, 2016;Rosciano et al, 2018Rosciano et al, , 2019. However, interannual differences observed (especially in δ 13 C) were lower than the differences we observed for marine and terrestrial prey items.…”
Section: Limitationscontrasting
confidence: 64%
“…This is not totally unexpected, because use of oceanic areas was observed, mainly in female Rockhopper Penguins grouped in cluster 3 "oceanic". However, we would have expected higher d 13 C values for female Rockhopper Penguins foraging in cluster 1 "neritic" using near-shore foraging habitats, because, for instance, Magellanic Penguins foraging in similar areas presented higher d 13 C values in comparison (Rosciano et al 2018). Yet, the stable isotope data in this study integrate primarily the early chick-rearing period, so they may also include a portion from the late incubation period, during which female Rockhopper Penguins breeding at Isla de los Estados were located foraging to the south and east of the Island, reaching oceanic areas near the Polar Front and the Burwood Bank (Area Protegida Marina Namuncura), respectively (P€ utz et al 2006).…”
Section: Discussionmentioning
confidence: 90%
“…We evaluated this by exploring a multivariate clustering approach for statistically identifying different groups according to the foraging trip and diet (d 15 N) characteristics of each female. Across three breeding seasons, we used a combination of tracking and diving data from GPS and temperature and depth (GPS-TD) data loggers to obtain the track and diving profile of the penguins (e.g., Rosciano et al 2018), and d 13 C and d 15 N stable isotope analysis on whole blood samples to reveal the assimilated diet of the penguins for an extended period of time (Barquete et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although, we still cannot con rm this colony probably was founded by individuals from the nearby Año Nuevo Islands colonies, Observatorio or Goffré, which by historical records seemed to be older (Schiavini et al 2005, Balza et al 2022). These colonies are only 20 km away from the new site and thus within the foraging range for the species during chick rearing (Rosciano et al 2018), this precludes to lean toward the habitat quality hypothesis at least regarding foraging habitat. However, habitat quality in terms of nesting sites in Observatorio island could be deteriorated given bio-erosion by introduced rabbits (Balza et al 2022) and probably Magellanic penguins themselves (Quiroga et al 2020).…”
Section: Discussionmentioning
confidence: 99%